The Hypothalamic-Pituitary-Thyroid Axis in Infants and Children: Protection from Radioiodines. (25th May 2014) - Fisher, Jeffrey; Yang, Xiaoxia; Harris, Curtis; Koturbash, Igor; Lumen, Annie
Abstract : Potassium iodide (KI) is recommended as an emergency treatment for exposure to radioiodines, most commonly associated with nuclear detonation or mishaps at nuclear power plants. Protecting the thyroid gland of infants and children remains a priority because of increased incidence of thyroid cancer in the young exposed to radioiodines (such as 131 I and 133 I). There is a lack of clinical studies for KI and radioiodines in children or infants to draw definitive conclusions about the effectiveness and safety of KI administration in the young. In this paper, we compare functional aspects of the hypothalamic-pituitary-thyroid (HPT) axis in the young and adults and review the limited studies of KI in children. The HPT axis in the infant and child is hyperactive and therefore will respond less effectively to KI treatment compared to adults. Research on the safety and efficacy of KI in infants and children is needed.